Transcriptional circuits in B cell transformation - Hu, Yeguang (Curr Opin Hematol, 2017)
Loss of IKAROS in committed B cell precursors causes a block in differentiation while at the same time augments aberrant cellular properties, such as bone marrow stromal adhesion, self-renewal and resistance to glucocorticoid-mediated cell death. B cell acute lymphoblastic leukemias originating from these early stages of B cell differentiation and associated with IKAROS mutations share a high-risk cellular phenotype suggesting that deregulation of IKAROS-based mechanisms causes a highly malignant disease process. Recent studies show that IKAROS is critical for the activity of super-enhancers at genes required for pre-BCR signaling and differentiation, working either downstream of or in parallel with B cell master regulators such as EBF1 and PAX5. IKAROS also directly represses a cryptic regulatory network of transcription factors prevalent in mesenchymal and epithelial precursors that includes YAP1, TEAD1/2, LHX2 and LMO2, and their targets, which are not normally expressed in lymphocytes. IKAROS prevents not only expression of these “extra-lineage” transcription factors but also their co-operation with endogenous B cell master regulators, such as EBF1 and PAX5, leading to the formation of a de novo for lymphocytes super-enhancer network. IKAROS coordinates with the Polycomb repression complex (PRC2) to provide stable repression of associated genes during B cell development. However, induction of regulatory factors normally repressed by IKAROS starts a feed-forward loop that activates de novo enhancers and elevates them to super-enhancer status, thereby diminishing PRC2 repression and awakening aberrant epithelial-like cell properties in B cell precursors. Insight into IKAROS-based transcriptional circuits sets new paradigms for cell differentiation but also provides new approaches for classifying and treating high-risk human B-ALL that originates from these early stages of B cell differentiation